Pelatihan Pengolahan Dan Visualisasi Data Assessment Berbasis Google Form Di Buayan - Siti Fatimah; Novia Umu Sholikhah (Ar-Rihlah: Jurnal Inovasi Pengembangan Pendidikan Islam, 2021)
Data processing is one of the most important aspects in the assessment stage. The existence ofdata processing and visualization will make it easier to read the assessment results. Thisservice is carried out to provide knowledge and training on processing and visualizingassessment data based on google form at the MWC NU institution, Buayan District, KebumenRegency. The subject in this service is Syuriyah (supervisory board) at MWC NU Buayan.This service is carried out for two days through four stages, namely planning, preparation forimplementation/implementation, and evaluation/reflection. The results of the service showthat Syuriyah can process and visualize assessment data well. Processing and visualization ofassessment data is the key in providing recommendations from the results of monitoring andevaluation.